شکیل بدایونی کی نعتیہ شاعری میں لفظیات کا مطالعہ - Bibi, Dr. Naeemia (Zoraiz, 2022)
Words are the expression of human thought. Human thought becomes meaningful when it is composed in words. Both words and writing are the means of written expression of their author. In Naat Rasool Maqbool (peace be upon him), love and devotion are expressed by the word itself. Shakeel Badauni is distinguished among the progressive poets. Five of his poetry collections were published. Five of his poetry collections were published, but his third poetry collection "Naghma Firdous" (1947) is based on Natia poetry. In which his fine diction come to the fore. In his Naat, the words and phrases and the structure of the stanzas are very meaningful. Shakeel Badayoni has received grace from his contemporary poets. However, the dialectics of the Naat is unique from the contemporary poets. Because he has informed the word and meaning in Naat with new concepts keeping in mind the contemporary requirements. In imitation of the poetic tradition, the vocabulary found in them also has a new harmony. In this paper, a critical study of the Diction in Natia poetry of Shakeel Badayuni will be done.